Grinding performance of AISI D6 steel using CBN wheel vitrified and resinoid bonded - Sato, Bruno Kenta [UNESP]; Rodriguez, Rafael Lemes [UNESP]; Talon, Anthony Gaspar [UNESP]; Lopes, Jose Claudio [UNESP]; Mello, Hamilton Jose [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2019)
In the last decades, manufacturers attracted much attention to developing processes with competitivity, sustainability, and productivity. One of the most important developments was related to employing more efficient tools. CBN was developed to improve the performance of the abrasive materials by higher hardness, thermal conduction, and chemical stability. In this sense, not only abrasive grains' properties are important for tool performance, but also bonds are essential for the consolidation of CBN abrasives in manufacturing industry. In order to contribute to findings about the performance of applied bonds in CBN grinding wheels, this work aims to compare CBN grinding wheels composed of vitrified bond and resinoid bond. The workpiece material was AISI D6 special steel which is widely used to manufacture stamping matrix, and this application requires parts with high geometrical and dimensional precision, also high-quality surface finish. For the results analysis and discussion, tangential grinding force and acoustic emission were monitored in order to analyze the process efficiency and surface roughness and G ratio was measured; besides scanning electron, confocal microscopy and optical microscopy were used for the analysis of the ground surface. The vitrified bond provided more efficient results in terms of surface roughness and G ratio in comparison with resinoid bond. However, acoustic emission and tangential grinding force were lower in grinding with CBN resinoid bond what indicated lower mechanical loads. Therefore, this paper presents relevant information to select the appropriate bond to CBN grinding wheel application.
Keywords: Peripheral surface grinding; CBN grinding wheel; Vitrified bond; Resinoid bond; Acoustic emission; G ratio